THE POTENTIAL ROLE OF SPHINGOMONAS PAUCIMOBILIS IN BIOREMEDIATION OF SOILS CONTAMINATED WITH HYDROCARBON AND HEAVY METAL: Bioremediation using Sphingomonas paucimobilis - Jaafar, Raghad Shubbar (Malaysian Journal of Science, 2019)
Aiming to find the solution to the problem of soil polluted by hydrocarbons and the associated heavy metals, the present study focused on the biodegradation and bioremediation capability of Sphingomonas paucimobilis. Morphological and biochemical tests have been used to identify bacterial isolates and to confirm that an automated instrument for bacterial identification (Vitek II) has been used. Based on the results, the bacteria were identified as Sphingomonas paucimobilis. The bioremediation capacity was monitored: the lowest inhibitory concentration (MIC) of lead (Pb) and cadmium (Cd) followed by an assay of the removal capacity of S. paucimobilis using the atomic absorption spectrometry (AAS) analyzer. The bacteria showed higher MIC value for Pb (2000 ppm) the Cd (500 ppm). The percentage of removal for Pb and Cd were 27.95% and 58.78%, and 22.37% and 48.21% for the concentration 25 ppm and 50 ppm, respectively. These findings showed the high aliphatic hydrocarbon biodegradation capacity of S. paucimobilis, with the percentage of degradation being 48.15% and 63.40% of the concentration of crude oil by 2% and 5%, respectively. S. paucimobilis can potentially be a safe biological treatment strategy to remediate soil polluted with hydrocarbons in crude oil extraction sites.